A Structural and Morphological Analysis of the Road Network of Ancient Mountain Towns: A Case Study of China’s Longxing Town - Dai Xin; Tang Luojie; Tan Wenyong (Lodz University of Technology Press, 2023)
The morphological evolution of the road network of the ancient mountain town is the dynamic expression of the regional characteristics and the social and economic development. Based on the integration, integrated core and intelligibility of spatial syntax, this article analyzes the topology and the morphological change of the road network at Longxing town in Chongqing, China in 2009, 2016 and 2021. The morphological analysis is combined with the road network density, turning degree, the turning ratio and twisting ratio. The quantitative analysis demonstrates that: (1) The overall road network of the ancient town grows in a network and develops outwards to the south. (2) Its integrated core also moves south with the southward expansion of the road network. Consequently, the attraction point changes to the south, and the attraction of the original integrated core becomes lower. (3) Its density is increasing year by year; while the turning degree is decreasing year by year. In consequence, the morphological evolution of the road network of the ancient mountain town is regularized. Finally, based on the above structural and morphological analysis, we propose the corresponding protection and development strategy of the road network in the ancient mountain town.
Keywords: structural and morphological analysis; morphological evolution of the road network; ancient town in the mountains; Longxing ancient town; analiza strukturalna i morfologiczna; ewolucja morfologiczna sieci drogowej; starożytne miasto w górach; starożytne miasto Longxing